Implementation of the Short Surah Memorizing Habit Method in Religious and Moral Development at RA Mamba'ul Hidayah Pati - Afti Hilya Maulida; Mustakimah Mustakimah; Mursid Mursid (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
This study aims to examine the process of applying the habituation method in memorizing short surahs for early childhood at RA Mamba'ul Hidayah Pati and how the method contributes to the development of children's religion and morals. This study uses a descriptive qualitative approach. The primary data sources in this study were obtained through interviews with those observed, which aimed to observe directly at the research location. The research conducted at RA Mamba'ul Hidayah Pati revealed that this method is effective in facilitating children's memorization through fun repetition, accompanied by explanations of the meaning of the surah that are in accordance with the child's understanding. In this habituation, it shows that the ability to memorize short surahs by applying the memorization habituation method will make it easier for children because children memorize by repeating the readings that have been memorized by reading short surahs that will be memorized repeatedly will make it easier for the child to remember what has been read by the child. And the role of parents at home is very important because it provides motivation and encouragement to children so that children are diligent in memorizing short surahs at home.